Mindfulness-Based Cognitive Therapy (MBCT) for Reducing Symptoms and Preventing Relapse of Depressive Disorders: A Literature Review - Takdir, Annisya Muthmainnah (Fathana, 2025)
Depressive disorder is one of the most prevalent mental health problems with a significant impact on quality of life. In Indonesia, the 2018 National Health Survey (Riskesdas) reported a prevalence of depression among adolescents at 6.2%, with risk increasing along with age. The high relapse rate makes depression a chronic condition that requires long-term intervention strategies. Mindfulness-Based Cognitive Therapy (MBCT) has emerged as an evidence-based intervention that integrates cognitive-behavioral therapy with mindfulness practices to help individuals disengage from ruminative thought patterns. This article aims to review empirical evidence regarding the effectiveness of MBCT in reducing depressive symptoms and preventing relapse. The method employed is a narrative review of scientific articles published between 2000 and 2020, encompassing randomized controlled trials (RCTs), quasi-experimental studies, case studies, and meta-analyses. Data collection was carried out by examining documentation from previous studies through database searches such as Google Scholar, Sinta, Science Direct, and Taylor & Francis. The review findings indicate that MBCT is effective in reducing depression, anxiety, and rumination, improving quality of life and self-compassion, and demonstrates comparable effectiveness to conventional cognitive therapy and pharmacotherapy in preventing relapse. These findings strengthen MBCT’s position as a clinical and preventive intervention with potential for implementation in mental health services in Indonesia.